ROTAVIRUS INFECTION. HOW TO REALLY PROTECT CHILDREN FROM SEVERE GASTROENTERITIS? - T. A. Grechukha; M. G. Galitskaya; A. G. Gayvoronskaya; L. S. Namazova-Baranova (Педиатрическая фармакология, 2013)
According to the statistics of the recent 5 years, the share of rotavirus gastroenterites is 44-47% of all acute intestinal infections in children under 5 years of age in the Russian Federation. Up to 5% of mortality rate in children under 5 years of age is connected with rotavirus gastroenteritis. Rotavirus gastroenteritis takes an especially severe course in children of 6-24 months of age. The only reliable method of preventing this infection is vaccination. The authors present information on the rotavirus strains dominant in Russia and abroad, efficacy and safety of immunization with a pentavalent vaccine and the recommended schemes of its administration. This vaccine is registered in the Russian Federation; it is to be first used in the nearest future.